2004
DOI: 10.1097/01.aog.0000128904.40103.e8
|View full text |Cite
|
Sign up to set email alerts
|

Tension-Free Vaginal Tape and Laparoscopic Mesh Colposuspension for Stress Urinary Incontinence

Abstract: Treatment with TVT results in higher objective and subjective cure rates at 1 year than treatment by means of laparoscopic mesh colposuspension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 25 publications
0
47
0
2
Order By: Relevance
“…In contrast, a deterioration of the effectiveness was reported by Alcalay et al [7], Valpas et al [18], El Toukhy et al [19], and Kjolhede et al [8] for LBC. Burton et al [20] have similar results with increasing follow-up, whereas the open procedure showed no decrease in efficacy after the same time interval.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, a deterioration of the effectiveness was reported by Alcalay et al [7], Valpas et al [18], El Toukhy et al [19], and Kjolhede et al [8] for LBC. Burton et al [20] have similar results with increasing follow-up, whereas the open procedure showed no decrease in efficacy after the same time interval.…”
Section: Discussionmentioning
confidence: 88%
“…There are many studies evaluating TVT and sling methods, but the majority are retrospective observational studies and not randomized controlled trials [18][19][20] . However, there are a few randomized studies comparing TVT with other procedures [21][22][23][24] . AbdelFattah et al [21] have compared TVT with pelvicol pubovaginal sling in 142 patients and reported equal success rates (90%) in the 3-year follow-up for both, but one main criticism of the study was the subjective assessment of the success rate from a questionnaire answered by patients.…”
Section: Discussionmentioning
confidence: 99%
“…AbdelFattah et al [21] have compared TVT with pelvicol pubovaginal sling in 142 patients and reported equal success rates (90%) in the 3-year follow-up for both, but one main criticism of the study was the subjective assessment of the success rate from a questionnaire answered by patients. Valpas et al [22] compared TVT with laparoscopic mesh colposuspension and reported success rates of 85.7 and 56.9%, respectively, using an objective 24-hour pad test. However, the follow-up was only 1 year and the surgery was performed in 6 medical centers by different surgeons in contrast to 1 surgeon in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous randomized clinical trials [1][2][3][4][5] have shown the tension-free vaginal tape (TVT) to be equally or more efficacious than traditional surgical procedures for female stress urinary incontinence (SUI). Many feel that these trials, the minimally invasive nature of the procedure, and its favorable long-term objective success [6] have established TVT as a new gold standard in the treatment of SUI.…”
Section: Introductionmentioning
confidence: 99%